"Fiber-in-tube" hierarchical nanofibers based on defect-rich bimetallic oxide@C bubbles: a high-efficiency and superior performance cathode for hybrid Zn batteries. Issue 28 (13th July 2020) - Zhou, Yang; Song, Yu; Zhang, Sen; Deng, Chao
Abstract : "Fiber-in-tube" hierarchical structured nanofibers based on defective bimetallic oxide@C bubbles are a highly efficient and high-performance cathode for flexible hybrid Zn batteries. Abstract : The exploration of novel cathodes with high efficiency and superior energy storage is a crucial issue for hybrid Zn batteries (HZBs). Herein, novel fiber-in-tube hierarchical nanofibers composed of defect-rich NiCo2 O4− δ @C bubbles (DBHF) are constructed as the HZB cathode. The nanoscale bimetal oxide bubbles with a defective structure are surrounded by a porous carbon network, which connect with each other and assemble a fiber-in-tube hierarchical configuration. The DBHF nanofiber not only provides a highly porous and conductive skeleton for fast electron/ion transport, but also possesses rich active sites to accelerate oxygen reduction/evolution reactions (ORR/OER). Benefitting from both electrochemical and electrocatalytic properties, the fabricated HZB with the DBHF cathode exhibits a high operating voltage, fast kinetics and high energy density. In addition, the two-set charge/discharge curves during long-term cycles further demonstrate its good stability and high efficiency. More impressively, the wide environmental adaptation and excellent "air-charging" capability make the prepared flexible hybrid Zn battery an uninterrupted power source for flexible electronics under different working conditions. Therefore, this work provides a novel high-performance cathode for HZBs and propels the development of flexible batteries towards multiple applications.